The effect of eyebrow stenting on the measurement of levator excursion in normal and ptotic eyelids. (3rd September 2019) - Yeganeh, Amir; Sinha, Kunal R.; Fell, David; Rootman, Daniel B.
ABSTRACT: Introduction : Levator function is classically estimated by measuring upper eyelid excursion (ULE) with digital brow stenting. The purpose of this study is to compare ULE with and without brow stenting in normal and ptotic eyelids. Methods : In this prospective observational study, normal and ptotic eyelids were recruited. Subjects were photographed with and without digital brow stenting in primary position, downgaze, and upgaze. Measurements were conducted on digital photographs. The primary outcome measure was ULE (distance travelled by the eyelid margin between downgaze and upgaze). Normal and ptosis (MRD1 ≤ 2.5 mm or asymmetry ≥ 1 mm) subgroups were defined. Independent one-way ANOVA and independent samples t -tests were performed. This study was powered to detect a 1 mm difference in the primary outcome measure, assuming SD = 1 mm, with alpha = 0.05 and beta-error = 0.95. Results : Twenty-eight normal eyelids of 22 subjects and 28 ptotic eyes of 18 subjects were included. Stenting significantly ( p  < 0.01) increased ULE in the overall sample (+0.9 mm) and in controls (+1.2 mm), but not ( p  > 0.05) in ptotic eyelids (+0.5 mm). Post hoc analysis revealed a beta-error of 0.08 in the latter. Conclusion : ULE was significantly higher with brow stenting in normal eyelids (approximately +1.2 mm) but not in ptotic eyelids, possibly due to increased levator tone secondary to increased effort in the coupled frontalis.